Penggunaan Web Carrd.co untuk Mendesain Media Pembelajaran yang Ramah Pengguna dan Berbasis Web - Kholifatunnisa Assholihah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study discusses the use of the Carrd.co website as a user-friendly web-based learning medium for delivering short story material in the Indonesian Language Learning Media course. Carrd.co was chosen due to its ease of access, simple interface, and flexibility in designing interactive web pages. The study was conducted using a qualitative descriptive approach through the stages of needs analysis, media design, trials, and evaluation. The results show that Carrd.co is able to provide short story learning media that is attractive, easily accessible, and increases student engagement.